A SYSTEMATIC REVIEW OF FREE WRITING TO TEACHING WRITING - Elda Fanisa Putri; Tri Kurniawati; Ageung Darajat (XXXX-XXXX, 2021)
This research aimed to find out the contribution of free writing technique to teaching writing. A systematic review method was applied in this research. Thesubjectof this research was five studies selected by inclusion and exclusion criteria. This research reviewed five published selected studies related to free writing technique in teaching writing from year 2010 to 2018.The researcher founds the related studies (journals) manually by using search engine google scholar with keywords searching “Free Writing technique” to find the journals and using zotero software as a tool to collect and select the journals.The researcher used thematic analysis to analyze the data.The research findings showed that freewriting technique contributes helps students to overcome fears of making mistakes in writing, release inner tension, reduce students’ writing anxiety, facilitate the students to focus in generating and exploring the ideas, make the students enjoyed the activity, and beneficial for learning English. Last but not least, free writing increase the students speed of writing and flow of thought. Moreover, it increase students’ writing fluency, improve students’ writing confidence. Keywords : Free Writing, Systematic Review, Writing